School Professionals' Knowledge and Beliefs About Youth With Chronic Illness. (10th July 2018) - Berger, Carolyn; Valenzuela, Jessica; Tsikis, Joanna; Fletcher, Cynthia
ABSTRACT: BACKGROUND: Existing research demonstrates that youth with chronic illness often experience challenges including poor academic performance, attendance, and social success. However, past research demonstrates a lack of support for teachers to best educate students with chronic illness. In this study, we aim to describe the needs of local educators when working with students with chronic illness. METHODS: A questionnaire was completed by 383 middle or high school professionals. Responses were analyzed using descriptive statistics. ANOVA was used to examine differences between school professional groups and chronic illness types. RESULTS: Participants tended to disagree that students with chronic illness faced challenges in school and agreed that they had enough support to meet students' needs. They tended to agree that more collaboration between the health care team, schools, and families was needed. Participants reported feeling least prepared in working with students who had cystic fibrosis, epilepsy, or sickle cell disease. School nurses were more likely to recognize the challenges, supports, and collaboration needed. CONCLUSIONS: More training and support is needed for school professionals in their work with students with chronic illness. Assessments may be useful at a local level to help schools develop better policies and plans for educating youth with chronic illness.